Simulations of Bio-Micro High Power Density Power Generation System for Zero Energy Building - pujowidodo, hariyotejo; Siswantara, Ahmad Indra; -, Budiarso (Universitas Indonesia, 2019)
The study of bio-micro high power density power generation system simulations for Zero Energy Building (ZEB) has been done, by analyzing the improvement momentum parameters for rotating impulse power turbines refers to the potential local bio-renewable energy sources. The main improvement parameters which are velocity and mass flow, would be analyzed in dynamic simulations of the thermal power generation system to give the estimated fuel rate requirement for appropriate heat enthalpy and predicted output power. Input parameters of simulation such as pressure, temperature, mass flow determined as design points of thermodynamics cycle. Using the fuel rate range 0.1 - 1 kg/s, LHV 12000 kJ/kg, and steam temperature from 120-165 oC, could predict the output power more than 300 kW. For power turbine demand range from 100 - 300 kW, it requires fuel rate 0.5-1 kg/s (LHV=12000 kJ/kg) and saturated steam pressure 360-700 kPa. This simulation model could give the conceptual design of thermal power generation for ZEB.